Anxiety Disorders are Associated with Reduced Heart Rate Variability: A Meta-Analysis - Chalmers, John A.; Quintana, Daniel S.; Abbott, Maree J.-Anne; Kemp, Andrew H. (Frontiers in Psychiatry, 2014)
Background: Anxiety disorders increase risk of future cardiovascular disease (CVD) and mortality, even after controlling for confounds including smoking, lifestyle, and socioeconomic status, and irrespective of a history of medical disorders. While impaired vagal function, indicated by reductions in heart rate variability (HRV), may be one mechanism linking anxiety disorders to CVD, prior studies have reported inconsistent findings highlighting the need for meta-analysis. Method: Studies comparing resting state HRV recordings in patients with an anxiety disorder as a primary diagnosis and healthy controls were considered for meta-analysis. Results: Meta-analyses were based on 36 articles, including 2086 patients with an anxiety disorder and 2294 controls. Overall, anxiety disorders were characterised by lower HRV (high frequency: Hedges’ g = -.29. 95%CI: -.41 to -.17, p < 0.001; time domain: Hedges’ g = -0.45, 95%CI: -0.57 to -0.33, p < .001) than controls. Panic Disorder (n=447), Post-Traumatic Stress Disorder (n=192), Generalized Anxiety Disorder (n=68), and Social anxiety disorder (n=90), but not Obsessive Compulsive Disorder (n=40), displayed reductions in high frequency HRV relative to controls (all ps < .001). Conclusions: Anxiety disorders are associated with reduced HRV, findings associated with a small to moderate effect size. Findings have important implications for future physical health and wellbeing of patients, highlighting a need for comprehensive cardiovascular risk reduction.